# Chain relation in three variables

I would like to prove the following identity, where $x,y,z$ are linked by a functional relation $f(x,y,z)=0$ and where the parentheses denote differentiation while keeping the indicated variable constant:

$$\left(\frac{\partial x}{\partial y}\right)_z \left(\frac{\partial y}{\partial z}\right)_x \left(\frac{\partial z}{\partial x}\right)_y=-1$$

Can you help?

-
For searching purposes: this chain relation is often attributed to Euler; thus the terms "Euler relation" or "Euler chain relation" are sometimes used. – J. M. Apr 15 '12 at 15:58

Let $A_t=\dfrac{\partial f}{\partial t}$ for $t$ in $\{x,y,z\}$, then $$\left(\frac{\partial x}{\partial y}\right)_z=-\frac{A_y}{A_x},\qquad\left(\frac{\partial y}{\partial z}\right)_x=-\frac{A_z}{A_y},\qquad\left(\frac{\partial z}{\partial x}\right)_y=-\frac{A_x}{A_z}.$$ The result follows.
To prove the first identity for example, assume that $x=x^*+a$, $y=y^*+b$ and $z=z^*$ solve $f(x,y,z)=0$ with $a\to0$ and $b\to0$. Then $\dfrac{a}b\to\left(\dfrac{\partial x}{\partial y}\right)_z$ and $$0=f(x^*+a,y^*+b,z^*)-f(x^*,y^*,z^*)=aA_x+bA_y+o((a,b)),$$ hence $$\dfrac{a}b\to-\dfrac{A_y}{A_x}.$$
isn't $\dfrac{a}b$ going to $+\dfrac{A_y}{A_x}$ instead of $-\dfrac{A_y}{A_x}$? – sjdh Dec 10 '12 at 9:33
sorry, I copied the wrong formulae from you post. I meant Isn't $\dfrac{a}b\to$ going to $+\left(\dfrac{\partial x}{\partial y}\right)_z$ instead of $-\left(\dfrac{\partial x}{\partial y}\right)_z$ – sjdh Dec 10 '12 at 9:49